Conjugated microporous polymer and application thereof in degrading florfenicol
Through the synergistic photocatalytic system of conjugated microporous polymer CMP2-85 and sodium perdisulfate, the efficiency and cost problems of sulfate radical degradation of flufenicol were solved, and efficient and stable flufenicol was achieved. Nikau degradation, suitable for complex environmental water bodies.
Patent Information
- Application Number
- CN202411455325.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-18
- Publication Date
- 2024-12-31
AI Technical Summary
In the prior art, there is insufficient research on the degradation of frefenicol by sulfate radicals, lacks efficient, stable and reusable activators and oxidation mechanisms, and has high degradation efficiency and cost in complex environments.
The conjugated microporous polymer CMP2-85 with a specific structure formed a collaborative photocatalytic system, and the degradation of foxo is carried out through visible light activation, and the porous characteristics of CMP2-85 and the activation ability of PDS are used to achieve high efficiency. degradation.
It achieves efficient, stable and reusable degradation of frefenicol, with high degradation efficiency and low cost, and is suitable for complex environmental water bodies without secondary pollution.
Smart Images

Figure BDA0005090297720000011 
Figure BDA0005090297720000031 
Figure BDA0005090297720000041
Abstract
Description
Technical Field
[0001] The invention relates to the field of conjugated microporous polymers, and in particular to a conjugated microporous polymer and application thereof in degrading florfenicol. Background Art
[0002] Florfenicol (FLO: Florfenicol) is a new type of chloramphenicol broad-spectrum antibiotic with the advantages of high antibacterial activity and no potential toxicity. It is widely used in poultry farming, aquaculture and animal husbandry as a substitute for chloramphenicol. Although florfenicol is safer than chloramphenicol, it still has certain side effects, mainly manifested as embryotoxicity and a strong inhibitory effect on the animal's immune system. Due to the large-scale use of florfenicol in the animal husbandry and aquatic industries, it is frequently detected in the water environment, posing a serious threat to the ecological environment and human health.
[0003]
[0004] Since florfenicol has moderate hydrophilicity and poor biodegradability, it has good stability in the water environment and has a risk of migration. Therefore, it is of great significance to conduct in-depth research on the degradation method and mechanism of florfenicol and effectively eliminate the accumulated florfenicol in the water environment.
[0005] At present, the main treatment methods for water bodies affected by antibiotic pollution include adsorption, biological treatment, chlorination, and advanced oxidation process (AOPs). Adsorption is a method of removing pollutants by attaching pollutant molecules to the surface of solids. The reuse of commonly used adsorbent granular activated carbon (GACs) is difficult and costly. During the adsorption process, pollutants only transfer from liquid to solid phase to produce new solid residues. How to deal with such residues needs to be reasonably considered. Improper treatment can easily cause secondary pollution. Carbon nanotubes (CNTs) are another hot material in adsorption. Due to their high specific surface area, enhanced reactivity and modifiability, carbon nanotubes have been proven to be effective in many fields, especially in removing various pollutants such as antibiotics in water environments. Biological treatment is the most commonly used sewage treatment method in sewage treatment plants, but the activated sludge method is easily affected by highly toxic pollutants, which inhibits the degradation effect of antibiotics, and biological treatment is ineffective for many antibiotics. Chlorination is a common method for purifying water in water plants. This technology can effectively degrade low-concentration antibiotics, but other toxic products are often generated. Advanced oxidation technology uses free radicals generated in situ in the system to degrade antibiotics such as florfenicol. It has attracted attention in recent years due to its relatively high efficiency. Common AOPs mainly include ozone, Fenton and photo-Fenton, electrochemistry and persulfate technologies, which mainly produce a variety of active intermediates with strong oxidizing ability such as ·OH, SO4 -· 、O2 –· and O2 -In 2015, Professor Liu Ning of Shanghai University of Technology and others found that ultraviolet (UV) radiation hydrogen peroxide can effectively degrade florfenicol in water. Under the irradiation of a 300W high-pressure mercury lamp, the UV / H2O2 system can achieve a degradation rate of more than 95% within 1.5 hours (Ning Liu, Sasa Sijak, Ming Zheng, Liang Tang, Gang Xu, Minghong Wu, Chem. Eng. J., 2015, 260, 826-834.). In 2015, Professor Naiyun Gao and others from Tongji University found that compared with the UV / H2O2 system, the florfenicol solution treated with the UV / PDS (PDS: sodium persulfate, Na2S2O8, used to generate sulfate free radicals) system can achieve higher degradation efficiency and better mineralization rate (Yu-Qiong Gao, Nai-yun Gao, Yang Deng, Da-qiang Yin, Yan-sen Zhang. Environ. Sci. Pollut. Res., 2015, 22, 8693-8701.): more than 95% of florfenicol can be degraded within 45 minutes, and the mineralization rate of florfenicol reaches 58.8% after 2 hours, which is much higher than the 14% of the UV / H2O2 system, reflecting the significant advantages of sulfate free radicals. In 2018, Professor Cai Tianming and others from Nanjing Agricultural University found that cheap and readily available Fe3O4 can also efficiently activate persulfate to degrade florfenicol. Under the conditions of florfenicol initial concentration of 5.4 mg / L, pH 7.0, potassium persulfate concentration of 1.35 g / L, and Fe3O4 concentration of 1.0 g / L, the degradation rate of florfenicol was 89% at 120 min, and the mineralization rate at 240 min increased from 22% to 50% (Cai Hao. Research on the degradation of antibiotic florfenicol in water by Fe3O4-activated persulfate [D]. 2018, Nanjing Agricultural University.). These studies show that the use of AOPs to degrade florfenicol has good application prospects, but the existing AOPs method still has a lot of room for improvement. If an AOPs degradation system with high degradation rate and simple degradation environment can be developed, the degradation method and efficiency of florfenicol will be expanded.
[0006] Conjugated microporous polymers (CMPs) are a class of conjugated three-dimensional network polymers constructed entirely of organic molecules. Due to the rigidity of the conjugated units at the molecular level and the expansion of the conjugated structure, the network polymer skeleton can effectively support the porous channels and form inherent porous properties. Currently, CMPs materials have been widely studied in the fields of gas adsorption and energy storage, while there are relatively few studies on pollutant degradation. If CMPs can be studied more extensively and in-depth in the field of pollutant degradation, its advantages may be brought into play to improve the degradation efficiency and industrial application potential. Summary of the invention
[0007] At present, the research on the degradation of florfenicol based on sulfate radicals is obviously insufficient, and more and deeper research is urgently needed. At this stage, the following problems mainly exist: 1) The activation means of sulfate radicals are insufficient, and it is necessary to develop a new activator that is simple, easy to obtain, efficient, highly stable and reusable, as well as a more economical and efficient activation method, to reduce the processing cost and reduce the secondary pollution generated during the activation process. 2) The research on the oxidation mechanism is not systematic enough, and it is necessary to combine new advanced in-situ characterization techniques and theoretical calculation methods to conduct in-depth and systematic research on the generation, reaction pathways and oxidative degradation pathways of active free radicals. 3) The research on the effects of other substances and inorganic salt ions on the degradation efficiency in actual environmental wastewater is insufficient, and it is necessary to conduct photocatalytic degradation research of mixed systems or actual wastewater. In view of these existing problems, the present invention provides a conjugated microporous polymer (CMP2-85) of a specific structure, which can be combined with sodium persulfate to form a CMP / PDS synergistic photocatalytic system for the degradation of florfenicol, with high degradation efficiency, can be activated by common visible light, high efficiency, high stability and reusable characteristics, and is suitable for complex actual environmental water bodies.
[0008] The present invention also provides the application of the conjugated microporous polymer (CMP2-85) in the degradation of florfenicol. The application method is simple and easy to operate, the degradation efficiency is high, the degradation environment is simple, the cost is low, and it is suitable for large-scale promotion and application.
[0009] A conjugated microporous polymer (CMP2-85) is formed by alternating the structure represented by formula II and the structure represented by formula III in a π-conjugated form:
[0010]
[0011] The molar ratio of the structure represented by formula II to the structure represented by formula III is 2:3.
[0012] The conjugated microporous polymer may have a structural unit shown in the following formula I:
[0013]
[0014] The method for synthesizing the conjugated microporous polymer comprises: selecting 2,4,6-tris(4-ethynylphenyl)-1,3,5-triazine and 2,5-dibromophenol as building monomers, and preparing the conjugated microporous polymer by using an existing synthesis method of the conjugated microporous polymer or improving the existing synthesis method. Preferably, the method for synthesizing the conjugated microporous polymer comprises: synthesizing the conjugated microporous polymer CMP2-85 by using a hydrothermal method based on a Sonogashira reaction of 2,4,6-tris(4-ethynylphenyl)-1,3,5-triazine and 2,5-dibromophenol.
[0015] Preferably, the 2,4,6-tris(4-ethynylphenyl)-1,3,5-triazine and 2,5-dibromophenol can be fed in a molar ratio of 2:3.
[0016] The reaction is preferably completed under the catalysis of tetrakis(triphenylphosphine)palladium (Pd(PPh3)4) and cuprous iodide (CuI), which is more conducive to the reaction.
[0017] The reaction is preferably carried out in a solvent of dimethylformamide (DMF) and triethylamine (NEt3). Further preferably, the volume ratio of dimethylformamide to triethylamine is 2-3:1.
[0018] The reaction is preferably carried out under the protection of nitrogen or an inert gas.
[0019] The reaction conditions are preferably: 80° C.-120° C. for 12 h-24 h, more preferably 120° C. for 24 h.
[0020] The reactants were filtered to obtain a solid, which was washed with water and methanol, ultrasonically washed with methanol again, and then dried to obtain a conjugated microporous polymer CMP2-85.
[0021] The 2,5-dibromophenol in the present invention can be replaced by 2,5-diiodophenol substituted by other halogens such as iodine.
[0022] The conjugated microporous polymer can adsorb and / or degrade florfenicol, and can be used as a florfenicol adsorption material and / or a florfenicol degradation material, and can also be used to prepare a florfenicol adsorption material and / or a florfenicol degradation material. The florfenicol degradation material is a material that uses visible light for photocatalytic degradation. Preferably, the florfenicol degradation material includes the conjugated microporous polymer and sodium persulfate.
[0023] The conjugated microporous polymer can be used for adsorbing and / or degrading florfenicol, for example, can be used for adsorbing and / or degrading florfenicol in water.
[0024] The method for adsorbing florfenicol by the conjugated microporous polymer comprises: mixing the conjugated microporous polymer and a solution (such as water) containing florfenicol evenly, and completing the adsorption of florfenicol by the conjugated microporous polymer. Preferably, the mixing time is greater than or equal to 30min. Further preferably, the mixing time is greater than or equal to 30min and less than or equal to 60min. Generally, adsorption equilibrium is basically reached in 60min, and further increasing the mixing time has no obvious effect on the adsorption effect. Suitable adsorption time can be selected according to the field of application. Preferably, the usage of the conjugated microporous polymer is at least 0.5mg for every 0.4mg of florfenicol, further preferably, 0.5mg-4mg is used for every 0.4mg of florfenicol, and most preferably 2mg-4mg is used for every 0.4mg of florfenicol, and further increasing the usage has no obvious effect on the adsorption effect. The solution containing florfenicol can use water containing florfenicol.
[0025] The conjugated microporous polymer is used in combination with sodium peroxydisulfate and uses visible light photocatalysis to degrade florfenicol. The application method includes: mixing the conjugated microporous polymer with the water containing florfenicol, adding sodium peroxydisulfate, and irradiating the solution with 420nm-780nm visible light to degrade florfenicol. Alternatively, the application method includes: mixing the conjugated microporous polymer with the water containing florfenicol, adsorbing it in a dark place, adding sodium peroxydisulfate and irradiating the solution with 420nm-780nm visible light to degrade florfenicol. Preferably, the time for irradiating the solution with visible light is greater than or equal to 30min. Further preferably, the time for irradiating the solution with visible light is 30min-120min. Most preferably, the time for irradiating the solution with visible light is 120min, and further increasing the irradiation time has no significant effect on the degradation effect. Preferably, for every 0.4mg of florfenicol, the amount of the conjugated microporous polymer used is at least 0.5mg, and the amount of the sodium peroxydisulfate used is at least 0.047g. Further preferably, for every 0.4 mg of florfenicol, the amount of the conjugated microporous polymer used is at least 0.5 mg-4 mg, and the amount of the sodium persulfate used is 0.047 g-0.238 g; most preferably, for every 0.4 mg of florfenicol, the amount of the conjugated microporous polymer used is at least 2 mg-4 mg, and the amount of the sodium persulfate used is 0.119 g-0.238 g. Increasing the amount used has no significant effect on the degradation effect. The light-proof adsorption time is preferably greater than or equal to 30 min, and more preferably greater than or equal to 30 min and less than or equal to 60 min.
[0026] Preferably, when the conjugated microporous polymer is used in combination with sodium peroxodisulfate and visible light is used to photocatalytically degrade florfenicol, the pH of the florfenicol-containing solution is adjusted to 3-11.
[0027] Compared with the prior art, the present invention has the following beneficial effects:
[0028] The conjugated microporous polymer CMP2-85 with a specific D-π-A type structure of the present invention has visible light responsiveness and can be combined with sodium persulfate to form a CMP2-85 / PDS synergistic photocatalytic system for visible light photocatalytic degradation of florfenicol. The system has high degradation efficiency, good mineralization rate, can be activated by common visible light, is highly efficient, highly stable and reusable, and is suitable for complex actual environmental water bodies.
[0029] The conjugated microporous polymer CMP2-85 of the present invention can be used for adsorption and / or degradation of florfenicol, the application method is simple and easy to operate, the degradation efficiency is high, the mineralization rate is good, the degradation environment is simple, the conjugated microporous polymer CMP2-85 is reusable and has low cost, and is suitable for large-scale promotion and application. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 The synthetic route of CMP2-85 of the present invention is shown in FIG.
[0031] Figure 2 This is a SEM image of CMP2-85 of the present invention at a resolution of 1 μm;
[0032] Figure 3 This is a SEM image of CMP2-85 of the present invention at a resolution of 500 nm;
[0033] Figure 4 N2-BET spectrum of CMP2-85 of the present invention;
[0034] Figure 5 This is a micropore size distribution diagram of CMP2-85 of the present invention;
[0035] Figure 6 The infrared spectrum of CMP2-85 and its raw materials of the present invention;
[0036] Figure 7 is the EDS spectrum of CMP2-85 of the present invention;
[0037] Figure 8 is the UV-visible spectrum of CMP2-85 of the present invention;
[0038] Fig. 9 VB-XPS spectrum of CMP2-85 of the present invention;
[0039] Fig.10 is the conduction band potential diagram of CMP2-85 of the present invention;
[0040] Fig.11 This is a transient photocurrent response diagram of CMP2-85 of the present invention;
[0041] Fig.12 This is a comparison chart of the adsorption and photocatalytic degradation effects of CMPs materials with different structures on florfenicol;
[0042] Fig.13 This is a comparison chart of the photocatalytic degradation effects of florfenicol in each experimental group; NoAdd represents the blank control group without adding CMP2-85 and PDS;
[0043] Fig.14 This is a comparison of the photocatalytic degradation effects of florfenicol using the commonly used photocatalysts TiO2 and g-C3N4 and CMP 2-85 in combination with PDS;
[0044] Fig.15 This is a graph showing the degradation effect of florfenicol when CMP2-85 is used in combination with PDS at different dosages;
[0045] Fig.16 This is a graph showing the degradation effect of florfenicol when PDS is used in combination with CMP2-85 at different dosages;
[0046] Fig.17 The adsorption and degradation effect of florfenicol by CMP2-85 combined with PDS in different pH solutions;
[0047] Fig.18 The adsorption and degradation effect of florfenicol on CMP2-85 combined with PDS in solutions with different competitive ions;
[0048] Fig.19 This is a diagram showing the degradation effect of florfenicol after repeated use of CMP2-85 of the present invention;
[0049] Fig. 20 This is a kinetic analysis diagram of the photocatalytic degradation of CMP2-85 of the present invention;
[0050] Fig.21 This is a diagram showing the quenching experimental results of the visible light catalytic degradation of florfenicol by the CMP2-85 / PDS synergistic photocatalytic system of the present invention;
[0051] Fig. 22 This is a graph showing the EPR detection results of the aqueous solution of the CMP2-85 / PDS synergistic photocatalytic system of the present invention after being irradiated with visible light for 5 minutes;
[0052] Fig.23 This is an EPR test result diagram of the aqueous solution of the CMP2-85 / PDS synergistic photocatalytic system of the present invention after being irradiated with visible light for 30 minutes;
[0053] Among them, Isotherm Linear Plot represents the isotherm linear plot, Adsorption is adsorption, Desorption is desorption, Relative Pressure (p / p o ) represents relative pressure, that is, the ratio of the pressure here to the standard atmospheric pressure, and Quantity Adsorbed represents the adsorption amount, the unit is cm 3 / g; BJH Desorption dV / dlog(W)Pore Volume represents adsorption-desorption curve, Halsey:Faas Correction is the correction method for pore size distribution data analysis, dV / dlog(W)Pore Volume is the pore volume under the differential of pore volume to the logarithm of pore size, Pore Width represents micropore diameter, in nm; Wavelength is wavelength, Binding Energy represents binding energy; Energy represents energy; Current represents transient photocurrent, Time represents time, second represents seconds, Light On represents light, Light Off represents no light, Dark represents light-proof environment, c(mg / L) represents florfenicol concentration in solution, Time of visible light exposure represents visible light exposure time, h represents hours, min represents minutes, c / c0(%), c t / c0(%) represents the concentration of florfenicol in the solution at different times, c, c t The percentage of the initial concentration c0 of florfenicol in the solution; Filter means the filter of 420-780nm; Magnetic Field means the magnetic field intensity, the unit is mT (millitesla); Intensity / au means the response intensity (au). DETAILED DESCRIPTION
[0054] The present invention is further described in detail below in conjunction with specific embodiments so that those skilled in the art can better understand the technical solutions of the present invention.
[0055] Reagents and instruments used in the experiment
[0056] Reagents: All chemicals were purchased from Shanghai Titan Technology Co., Ltd. and Anaiji Chemical & 3A (Anhui Zesheng Technology Co., Ltd.). All chemicals used were of analytical grade and used directly.
[0057] Instruments: Newbit Phchem III photochemical reactor (xenon lamp light source), high performance liquid chromatograph (Agilent 1260II), etc.
[0058] The conditions for the visible light photocatalytic degradation experiment using a xenon lamp to simulate natural light include: using a xenon lamp equipped with a filter to simulate the visible light wave of 420nm-780nm in natural light, the lamp power is 400W, the light power at the reaction tube is 4.10mW, and the light power density is 5.35mW / cm 2 .
[0059] Example 1
[0060] 1. Preparation of Conjugated Microporous Polymers
[0061] Based on the Sonogashira reaction, conjugated microporous polymers (CMPs) were prepared by hydrothermal synthesis. The synthesis route is shown in Figure 1 :
[0062] 2,4,6-tris(4-ethynylphenyl)-1,3,5-triazine (76.8 mg, 0.2 mmol), 2,5-dibromophenol (75.6 mg, 0.3 mmol), tetrakis(triphenylphosphine)palladium (Pd(PPh3)4 (1.4 mg, 0.001 mmol, added at 0.5% of the mol amount of 2,4,6-tris(4-ethynylphenyl)-1,3,5-triazine) and cuprous iodide (CuI, 0.8 mg, 0.004 mmol, added at 2% of the mol amount of 2,4,6-tris(4-ethynylphenyl)-1,3,5-triazine) were weighed into the inner lining of the hydrothermal reactor, and then 2 mL of dimethylformamide (DMF) and 1 mL of triethylamine (NEt3) solvent were added. Mix well and extract. After 1 minute of vacuum, N2 was filled in. Then the liner was ultrasonicated for 3 minutes to remove the air in the solvent. After repeated ventilation (N2) twice, the liner was placed in the reactor and tightened, and then the reactor was placed in an oven preheated to 120°C for 24 hours. After the reactor was cooled to room temperature, the reactor was opened to obtain a jelly-like black solid. After adding 10mL of water and stirring with a magnetic stirrer for 3 minutes, it was filtered and washed twice with 20mL of water and 20mL of methanol in turn. The solid was collected in the liner, 10mL of methanol was added and ultrasonicated for 5 minutes, then filtered and washed twice with an appropriate amount of methanol. The solid was dried in a vacuum drying oven at 80°C for 6 hours to obtain 89.2mg of the target product. Finally, the product was ground into powder using an agate mortar for use, recorded as CMP2-85.
[0063] 2. Characterization of CMP Materials
[0064] The physical phase of the material was characterized using techniques such as SEM, EDS and N2-BET, while the photoelectric properties of the CMPs material were tested using techniques such as UV-visible diffuse reflectance, VB-XPS and transient photocurrent response.
[0065] SEM images of material CMP2-85 at different resolutions are shown in Figure 2-Figure 3 , N2-BET spectrum see Figure 4 The micropore size distribution of the material is shown in Figure 5 , infrared spectra of materials and raw materials are shown in Figure 6 , EDS spectrum see Figure 7 .
[0066] from Figure 2 and Figure 3 It can be seen that CMP2-85 is a porous structure with different pore sizes. There are many smaller pores around the large pores and on the surface of the material. Figure 4 ) showed that the specific surface area of CMP2-85 was 855m 2 / g, the average pore size is 2.88nm (see Figure 5 ).
[0067] The infrared spectra of CMP2-85 and two monomers are shown in Figure 6 As shown, 3300cm in CMP2-85 -1 The small peak at 3380 cm-1 is the stretching vibration of OH, while in the raw material 2,5-dibromophenol it appears as a large broad peak at 3380 cm-1; -1 and 3237cm -1 The absorption peak near 846 cm is attributed to the stretching vibration peak of the ≡CH bond in the terminal alkyne in the monomer 2,4,6-tris(4-ethynylphenyl)-1,3,5-triazine, which disappears in CMP2-85. -1 The absorption peaks near the C-Br stretching vibration peak in the monomer 2,5-dibromophenol are not obvious in CMP2-87 and are significantly weaker than that in 2,5-dibromophenol, indicating that most of the C-Br bonds in CMP2-85 have disappeared, and only a small amount of incompletely reacted C-Br bonds exist; the bending vibration peak of the ≡CH bond in the terminal alkyne (648cm -1 ) is very obvious in the monomer 2,4,6-tris(4-ethynylphenyl)-1,3,5-triazine, but almost disappears in CMP2-85. Combined with the disappearance of the ≡CH stretching vibration peak, it shows that the content of terminal alkynes in CMP2-85 is very small. In summary, the obvious weakening of the ≡CH stretching, complete vibration peak and C-Br bond stretching vibration peak in CMP2-85 all indicate that CMP2-85 has been successfully synthesized and is a conjugated microporous polymer formed by alternating π-conjugated forms of the structure shown in formula II and the structure shown in formula III.
[0068] EDS spectrum (see Figure 7) shows that the content of transition metals Pd and Cu that have an activation effect on PDS in CMP2-85 is 0. The above data show that the large specific surface area and more small-sized pores of CMP2-85 ensure the adsorption performance of the material, and the activation of PDS by the material is achieved by the unique conjugated structure of the CMPs material itself under visible light irradiation, rather than the transition metals Pd and Cu that may be introduced during the synthesis process.
[0069] Photoelectric properties of materials: Test the photoelectric properties of CMP2-85: Calculate the band gap E of the material using the Tauc plot method from the UV-visible diffuse reflectance spectrum g is 2.51eV, and the absorption wavelength is mainly concentrated at 494nm, close to the green light wave (see Figure 8 ); The valence band of CMP2-85 was found to be 1.72 eV by valence band X-ray photoelectron spectroscopy (VB-XPS) test (see Fig. 9 ); and then calculated that the conduction band potential of the material is -0.79 eV (see Fig.10 ); From the transient photocurrent response of the material, it can be seen that CMP2-85 has good photocurrent response performance, and the photocurrent density is 0.17μA / cm 2 , indicating that the separation efficiency of photoinduced electron-hole pairs is high (see Fig.11 ). The above data show that CMP2-85 has good visible light response.
[0070] Comparative Example 1
[0071] The 2,4,6-tris(4-ethynylphenyl)-1,3,5-triazine and 2,5-dibromophenol monomers were replaced by the following alkynes and halides, respectively. The other operations were the same as in Example 1, and a series of conjugated microporous polymers were obtained, respectively, as follows: CMP1-146 (1,4-diethynylbenzene: cyanuric chloride = 3:2, molar ratio, all molar ratios are used below), CMP1-169 (1,3,5-triethynylbenzene: 5,5'-dibromo-2,2'-bipyridine = 2:3), CMP1-187 (1,3,5-triethynylbenzene: 2,4,6-tris-(4-bromophenyl)-[1,3,5]triazine = 1:1), CMP1-188 (2,4, CMP1-192 (2,4,6-tris(4-ethynylphenyl)-1,3,5-triazine: 2,6-dibromonaphthalene-1,4,5,8-tetracarboxylic dianhydride = 2:3), CMP1-197 (4,4'-diethynylbiphenyl: 2,5-dibromoterephthalic acid = 1:1), CMP2-86 (1,3,5-tris(4-ethynylphenyl)benzene: 2,5-dibromophenol = 2:3) and CMP2-87 (2,4,6-tris(4-ethynylphenyl)-1,3,5-triazine: 2,6-dibromonaphthalene-1,5-diol = 2:3).
[0072] Example 2
[0073] 1. Photocatalytic experiment
[0074] Florfenicol degradation experiment: 2mg CMP 2-85 and 20mL 20mg / L florfenicol aqueous solution (0.4mg florfenicol) were placed in a test tube, placed in a Newbit Phchem III photochemical reactor and stirred (350r / min), stirred for 1h under light-proof conditions, then sodium peroxydisulfate was added to make the final concentration of sodium peroxydisulfate 50mmol / L (sodium peroxydisulfate 0.238g), and the xenon lamp was turned on (adding a filter to filter out ultraviolet light, only retaining visible light at 420-780nm) to start the photocatalytic degradation experiment. Sampling was performed at regular intervals, and then an appropriate amount of methanol was added to the sample to quench the free radicals to terminate the photocatalytic degradation reaction. After filtering through a 13mm×0.45μm water filter membrane, the concentration of florfenicol in the filtrate was measured using a high performance liquid chromatograph.
[0075] 2. Screening of CMPs materials
[0076] The photocatalytic performance of the material CMP2-85 in Example 1 and the materials CMP1-146, CMP1-169, CMP1-187, CMP1-188, CMP1-192, CMP1-197, CMP2-86, and CMP2-87 (all using 2 mg) in Comparative Example 1 were screened using 20 mL of 50 mg / L florfenicol aqueous solution (1 mg florfenicol) according to the above photocatalytic experiment. The results are shown in Fig.12 In terms of total elimination rate, CMP2-85 had the best effect, up to 60%, which was significantly higher than the total elimination rate of 52% for CMP2-86, 47% for CMP2-87, 46.5% for CMP1-146, and 48% for CMP1-192 ( Fig.12 , the initial concentration of the florfenicol aqueous solution was 50 mg / L).
[0077] A control experiment was carried out using 20 mL of florfenicol aqueous solution according to the above photocatalytic experiment ( Fig.13 , the initial concentration of florfenicol aqueous solution is 20 mg / L): After 2 hours of illumination, the total elimination rate of florfenicol in the blank control group without CMP2-85 and PDS was only 3%; the total elimination rate of florfenicol in the control group with only CMP2-85 added was 51%, indicating that the photocatalyst CMP2-85 has good photocatalytic degradation performance; the total elimination rate of florfenicol in the control group containing only PDS was 49%; the total elimination rate of florfenicol in the experimental group containing both CMP2-85 and PDS was as high as 91%, indicating that the photocatalytic system of CMP2-85 combined with PDS can significantly improve the degradation efficiency of florfenicol.
[0078] The present invention also uses 20mL 20mg / L florfenicol aqueous solution to compare the performance of CMP2-85 with that of common photocatalysts according to the above photocatalytic experiment ( Fig.14 , the initial concentration of florfenicol aqueous solution is 20 mg / L): after 2 hours of illumination, the final degradation rate of the photocatalyst TiO2 combined with PDS is only 64%, the final degradation rate of the photocatalyst g-C3N4 combined with PDS is only 59%, and the final degradation rate of the CMP2-85 of the present invention combined with PDS is 91%, indicating that in the combined PDS degradation of florfenicol, the photocatalyst CMP 2-85 material of the present invention has more excellent performance.
[0079] The total organic carbon (TOC) in the solution of the CMP2-85+PDS system after 2 hours of illumination was measured using a total organic carbon (TOC) analyzer, and the mineralization efficiency of this method was 38%, which is an excellent performance. If the illumination time is increased, the mineralization efficiency of the reaction can be further improved.
[0080] 3. Investigation of factors affecting photocatalytic degradation
[0081] The present invention mainly investigates the effects of factors such as CMP2-85 dosage, PDS dosage, florfenicol initial solution concentration, light intensity and time, solution pH and competitive ions on the degradation of florfenicol in water by the CMP2-85 / PDS synergistic photocatalytic system.
[0082] 3.1 Effect of CMP 2-85 dosage on photocatalytic degradation of florfenicol in CMP2-85 / PDS system
[0083] The effect of CMP2-85 dosage on the degradation of florfenicol is shown in Fig.15 (20mL florfenicol aqueous solution with an initial concentration of 20mg / L, PDS dosage of 50mM (mM:mmol / L), CMP2-85 dosage increased from 0 to 0.2g / L, and the rest of the operations were performed according to the above photocatalytic experiment): As the CMP2-85 dosage increased from 0.025g / L to 0.2g / L, the total elimination rate of florfenicol increased significantly from 50% to more than 90%. The results show that for every 0.4mg of florfenicol, the amount of CMP2-85 used is preferably at least 0.5mg, more preferably 0.5mg-4mg, and most preferably 2mg-4mg.
[0084] 3.2 Effect of PDS dosage on photocatalytic degradation of florfenicol in CMP / PDS system
[0085] Different amounts of PDS will affect the amount of sulfate radicals produced, thereby affecting the degradation rate of florfenicol (the initial concentration of 20mL florfenicol aqueous solution is 20mg / L, the amount of CMP2-85 is 2mg, the PDS concentration is 0-50mM, and the rest of the operations are based on the above photocatalytic experiment). When the PDS concentration is in the range of 0-25mM, as the amount of PDS increases, the total elimination rate of florfenicol increases from 51% to 85%. When the PDS amount is 50mM, the total elimination rate of florfenicol increases to 91% ( Fig.16 ). However, when the amount of PDS was increased to a certain level, the total elimination rate of florfenicol did not increase significantly. It may be that too much persulfate in the system would react with SO4 .- Reaction, resulting in SO4 .- The production of did not increase exponentially, and the total elimination rate increased only slightly. The results showed that for every 0.4 mg of florfenicol, the amount of PDS used was preferably at least 0.047 g, more preferably 0.047 g to 0.238 g, and most preferably 0.119 g to 0.238 g.
[0086] 3.3 Effect of pH on photocatalytic degradation of florfenicol in CMP / PDS system
[0087] In the actual environment, the pH of wastewater is diverse, and the change of pH in water can not only change the existence form of antibiotics, but also affect the generation rate of active free radicals. Therefore, this experiment investigated the effect of different pH conditions on the CMP / PDS synergistic photocatalytic system (20mL florfenicol aqueous solution with an initial concentration of 20mg / L, pH = 1-11, CMP2-85 dosage of 2mg, PDS concentration of 50mM, and other operations according to the above photocatalytic experiment). The specific results are shown in Fig.17 : After being shielded from light for 1h and exposed to light for 2h, when pH=11, the adsorption performance and total elimination rate of CMP2-85 / PDS were improved; when pH=1, the adsorption performance of CMP2-85 / PDS was equivalent to that at pH=11, but the total elimination rate was reduced by more than 30%, indicating that strong acidic conditions inhibited the photocatalytic degradation performance. In general, when the pH was 3-11, the CMP 2-85 / PDS synergistic photocatalytic system showed a good degradation effect on florfenicol, indicating that pH had little effect on the degradation performance of the CMP 2-85 / PDS synergistic photocatalytic system on florfenicol.
[0088] 3.4 Effect of competitive ions on photocatalytic degradation of florfenicol in CMP / PDS system
[0089] In order to simulate the actual situation of water bodies, this experiment further studied the effect of low-concentration salt solution on the degradation of florfenicol by the CMP / PDS synergistic photocatalytic system (20 mL of florfenicol aqueous solution with an initial concentration of 20 mg / L, different concentrations of salt were added, the amount of CMP2-85 was 2 mg, the PDS concentration was 50 mM, and the rest of the operations were performed according to the above photocatalytic experiment). Fig.18 The results show that low concentration salt solutions such as NH4Cl, NaCl, Na2SO4, and NaHCO3 have no significant effect on the efficiency of CMP2-85 / PDS in degrading florfenicol, which reflects the good applicability of the CMP / PDS synergistic photocatalytic system.
[0090] Based on the above experimental results, when CMP2-85 is used to adsorb florfenicol, the mixing time of CMP2-85 and the solution is greater than or equal to 30min, and more preferably greater than or equal to 30min and less than or equal to 60min. Generally, adsorption equilibrium is basically reached in 60min, and further increasing the mixing time has no obvious effect on the adsorption effect. The appropriate adsorption time can be selected according to the field of application. When CMP2-85 is used for photocatalytic degradation of florfenicol by visible light irradiation, the time for visible light irradiation of the solution is greater than or equal to 30min, preferably 30min-120min, and most preferably 120min, and further increasing the irradiation time has no obvious effect on the degradation effect.
[0091] 3.5 Recyclability of photocatalysts
[0092] In addition to the technical requirement of excellent degradation performance, the cost of the degradation method must be considered in terms of economic efficiency. Therefore, the present invention studies the repeatability of the photocatalytic performance of the material: 2.0 mg CMP2-85 and PDS are added to 20 mL of 20 mg / L florfenicol aqueous solution to make the PDS concentration 50 mM, and the remaining operations are carried out according to the above photocatalytic experiment; after each experiment, CMP2-85 is filtered and collected, and the used CMP2-85 is washed with deionized water and methanol in turn and recovered, dried in a vacuum drying oven and used for the next cycle experiment. After three cycles of use, the total elimination rate is reduced from 91.7% to only 83.4% ( Fig.19 ), indicating that CMP2-85 has good reusability and has certain practical application prospects and economic benefits.
[0093] 3.6 Photocatalytic degradation kinetics
[0094] The degradation kinetics was studied under the optimal conditions of photocatalytic degradation (2.0 mg CMP2-85 and PDS were added to 20 mL of 20 mg / L florfenicol aqueous solution to make the PDS concentration 50 mM, and the rest of the operations were carried out according to the above photocatalytic experiment). The zero-order kinetic model (c0-c t = k0t), first-order kinetic model (ln(c0 / c t )=k1t) and the second-order kinetic model (1 / c t –1 / c0=k2t) to fit the degradation kinetic data. Fig. 20 (where c t is the concentration of florfenicol in the solution at time t, c0 is the initial concentration of florfenicol, t is the illumination time, k0, k1, k2 are the corresponding reaction rates). Fig. 20 It can be seen that the degradation of florfenicol in solution by CMP2-85 / PDS is a first-order reaction (the R 2 is 0.997), and the reaction rate is 0.78h -1 .
[0095] 3.7 Study on the mechanism of visible light photocatalytic degradation of florfenicol
[0096] Free radical quenching experiment: Under the optimal conditions for florfenicol degradation (add 2.0 mg CMP2-85 and PDS to 20 mL 20 mg / L florfenicol aqueous solution to make the PDS concentration 50 mM, set up multiple groups of experiments, add low concentrations (0.056 mM, equivalent to the concentration of florfenicol in the solution) of DDQ (2,3-dichloro-5,6-dicyano-1,4-benzoquinone, electron quencher), BQ (p-benzoquinone, ·O2 -Quencher), EDTA-2Na (hole h + quencher), methanol (·OH and SO4 ·- Quencher) and tert-butyl alcohol (·OH quencher), after a certain period of illumination, the concentration of florfenicol after visible light catalytic degradation was determined by liquid chromatography.
[0097] In-situ electron spin resonance (EPR) experiment: Weigh 2 mg of CMP2-85 material into a quartz reaction tube, add 20 mL of deionized water, then add 200 μL of 0.5 M (mol / L) Na2S2O8 aqueous solution and an appropriate amount of 5,5-dimethyl-1-pyrroline-N-oxide (DMPO) quencher. After stirring for 1 min, measure the data of 0 min in the dark, turn on the xenon lamp (add a filter to filter out ultraviolet light, leaving only visible light at 420-780 nm), and use a paramagnetic resonance spectrometer (Bruker EMXplus, Germany) to test after 5 min and 30 min under stirring conditions.
[0098] The free radical quenching experiment was used to detect whether the CMP2-85 / PDS synergistic photocatalytic system contained O2 ·- , ·OH, photogenerated electrons and holes and their role in degradation. Fig.21 As shown: After adding 2,2,6,6-tetramethylpiperidinyl oxide (TEMPO) and methanol, the final elimination rate of florfenicol decreased the most, from 90% to 63%, indicating the presence of ·OH in the system and that ·OH played a major role in the degradation of florfenicol. + After quenching with EDTA-2Na, the total elimination rate of florfenicol decreased from 90% to 70%, indicating that the hole h + It also contributes greatly to the degradation of florfenicol. After adding BQ, the total elimination rate decreased by about 5%, indicating that there is also O2 in the system. - Based on the above results, the present invention believes that the main active intermediates in the degradation of florfenicol by CMP2-85 / PDS are ·OH and hole h + .
[0099] To determine SO4 ·– The presence and magnitude of its effect, the present invention uses in-situ electron spin resonance (EPR) technology to directly detect SO4 in the system ·– and ·OH and other active free radicals, the results are shown in Fig. 22 and Fig.23 :With the increase of illumination time, the relative concentration of OH in the solution increased significantly, while SO4 ·– The content of SO4 did not increase significantly. The present invention believes that SO4 is indeed generated in situ in the system after illumination.·– and OH, and during the reaction SO4 ·– It will react with hydroxyl to form ·OH.
[0100] The present invention is based on the Sonogashira reaction, and synthesizes a series of conjugated microporous polymers CMPs with D-π-A type structures by a hydrothermal method, and forms a photocatalytic system with PDS, and utilizes the excellent adsorption performance, photocatalytic performance and high oxidizability of sulfate radicals of CMPs to photocatalytically degrade florfenicol under visible light. The photocatalytic system of CMP2-85 and PDS of the present invention has a significant excellent effect on the degradation of florfenicol. For a florfenicol solution (20 mL, 0.4 mg of florfenicol) with an initial concentration of 20 mg / L, 0.1 g / L of CMP2-85 (2 mg) and PDS can achieve an elimination rate of 90% or more of florfenicol after irradiation for 2 hours under visible light (420-780 nm), and a mineralization efficiency of 38% or more, and no secondary pollution will be generated, and CMP2-85 can be reused for 3 times and still maintain an elimination rate of more than 83%. The system is highly compatible with water pH and exhibits excellent degradation efficiency at pH 3-11. At the same time, low concentrations of salt have little effect on the degradation efficiency of the system, making it suitable for complex actual environmental water bodies. In summary, the CMP2-85 / PDS photocatalytic system is a mild, efficient, low-energy, and green method for degrading florfenicol.
Claims
1. A conjugated microporous polymer, characterized in that: The conjugated microporous polymer is formed by alternating the structure shown in Formula II and the structure shown in Formula III in a π-conjugated form:
2. Use of the conjugated microporous polymer according to claim 1 as a florfenicol adsorption material and / or a florfenicol degradation material.
3. Use of the conjugated microporous polymer according to claim 1 in preparing a florfenicol adsorption material and / or a florfenicol degradation material.
4. The use according to claim 2 or 3, characterized in that: The florfenicol degradation material is a material that uses visible light for photocatalytic degradation.
5. The use according to claim 4, characterized in that: The florfenicol degradation material comprises the conjugated microporous polymer and sodium peroxodisulfate.
6. Use of the conjugated microporous polymer according to claim 1 in the adsorption and / or degradation of florfenicol.
7. The use according to claim 6, characterized in that: Application of the conjugated microporous polymer in adsorbing and / or degrading florfenicol in water.
8. The use according to claim 6 or 7, characterized in that: The conjugated microporous polymer is used in combination with sodium peroxodisulfate and uses visible light to photocatalytically degrade florfenicol.
9. The use according to claim 8, characterized in that: include: After the conjugated microporous polymer is mixed with water containing florfenicol, sodium peroxydisulfate is added, and the solution is irradiated with visible light of 420nm-780nm to degrade florfenicol; or, after the conjugated microporous polymer is mixed with water containing florfenicol, it is adsorbed in the dark, sodium peroxydisulfate is added, and the solution is irradiated with visible light of 420nm-780nm to degrade florfenicol.
10. The use according to claim 9, characterized in that: The time for irradiating the solution with visible light is greater than or equal to 30 minutes.